Molecular adaptation during adaptive radiation in the Hawaiian endemic genus Schiedea. - Maxim V Kapralov; Dmitry A Filatov (PLoS ONE)
Background "Explosive" adaptive radiations on islands remain one of the most puzzling evolutionary phenomena. The rate of phenotypic and ecological adaptations is extremely fast during such events, suggesting that many genes may be under fairly strong selection. However, no evidence for adaptation at the level of protein coding genes was found, so it has been suggested that selection may work mainly on regulatory elements. Here we report the first evidence that positive selection does operate at the level of protein coding genes during rapid adaptive radiations. We studied molecular adaptation in Hawaiian endemic plant genus Schiedea (Caryophyllaceae), which includes closely related species with a striking range of morphological and ecological forms, varying from rainforest vines to woody shrubs growing in desert-like conditions on cliffs. Given the remarkable difference in photosynthetic performance between Schiedea species from different habitats, we focused on the "photosynthetic" Rubisco enzyme, the efficiency of which is known to be a limiting step in plant photosynthesis. Results We demonstrate that the chloroplast rbcL gene, encoding the large subunit of Rubisco enzyme, evolved under strong positive selection in Schiedea. Adaptive amino acid changes occurred in functionally important regions of Rubisco that interact with Rubisco activase, a chaperone which promotes and maintains the catalytic activity of Rubisco. Interestingly, positive selection acting on the rbcL might have caused favorable cytotypes to spread across several Schiedea species. Significance We report the first evidence for adaptive changes at the DNA and protein sequence level that may have been associated with the evolution of photosynthetic performance and colonization of new habitats during a recent adaptive radiation in an island plant genus. This illustrates how small changes at the molecular level may change ecological species performance and helps us to understand the molecular bases of extremely fast rate of adaptation during island adaptive radiations.